Spirituality, Distress and Posttraumatic Growth in Breast Cancer Patients - Paredes, Ana Cristina (Journal of religion and health, 2018)
Breast cancer is the most common type of cancer for women and is associated with increased distress. Spirituality and posttraumatic growth (PTG) have been associated with illness adjustment, but the relationship between these variables is still not well understood. A sample of 100 breast cancer patients completed a demographic and clinical questionnaire, the Posttraumatic Growth Inventory, Spiritual and Religious Attitudes in Dealing with Illness, and the Hospital Anxiety and Depression Scale. Results showed an association between PTG, spirituality and distress. Women with a longer diagnosis and recurrence showed more distress. Younger age, recurrent cancer and spirituality predicted higher PTG. Patients' spirituality should be part of intervention with breast cancer patients since it seems to be related to greater growth and adjustment to the illness.